The effect of Indomethacin and Betamethasone on the cytokine response of human neonatal mononuclear cells to gram-positive bacteria. Issue 1 (May 2015) - Ernst, Wolfgang; Kusi, Evelyn; Fill Malfertheiner, Sara; Reuschel, Edith; Deml, Ludwig; Seelbach-Göbel, Birgit
Highlights The effect of different drugs on the cytokine expression of CBMC after stimulation was evaluated. Betamethasone decreased production of pro-inflammatory cytokines. Indomethacin increased IL-10 production. A combination of both had a similar effect as Betamethasone alone. The cytokine expression differed depending on the gram-positive pathogen used for stimulation.